1976
DOI: 10.1044/jshd.4102.244
|View full text |Cite
|
Sign up to set email alerts
|

Critical Bandwidth and Sensitivity Prediction in the Acoustic Stapedial Reflex

Abstract: Critical bandwidth measurements and sensitivity prediction from the acoustic reflex (SPAR) test results were obtained on 20 normal-hearing and two groups of 10 hearing-impaired subjects each representing mild-to-moderate and severe hearing loss. Results of critical bandwidth measurements indicated that for center frequencies of 1000 and 2000 Hz the critical bandwidth was significantly greater for the hearing-impaired subjects. A statistical analysis of the differences in critical bandwidth between those predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

1977
1977
1984
1984

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Because middle ear abnormalities may affect the relation between the reflex thresholds for noise and tones," lo and Several studies5, 7, 9,11,13,[16][17][18] because the mentally retarded population has a greater incidence of middle ear problems than the population at large, efforts were made to eliminate any person with middle ear pathology. A prospective subject who had evidenced more than one episode of middle ear pathology for either ear over the past three years was rejected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because middle ear abnormalities may affect the relation between the reflex thresholds for noise and tones," lo and Several studies5, 7, 9,11,13,[16][17][18] because the mentally retarded population has a greater incidence of middle ear problems than the population at large, efforts were made to eliminate any person with middle ear pathology. A prospective subject who had evidenced more than one episode of middle ear pathology for either ear over the past three years was rejected.…”
Section: Methodsmentioning
confidence: 99%
“…Because middle ear abnormalities may affect the relation between the reflex thresholds for noise and tones," lo and Several studies5, 7, 9, 11,13,[16][17][18] 77…”
Section: Methodsmentioning
confidence: 99%
“…Based on acoustic reflex findings for I 156 ears, Jerger et al (1 1) concluded that with the SPAR method, hearing loss was predicted with reasonable accuracy. Probably as a result of this initial encouraging experience with SPAR and the obvious clinical attractiveness of an objective measure for estimating hearing loss, especially in children, the literature is replete with reports of clinical experience with both the original SPAR method (1,6,7,15,(22)(23)(24) and a modified version of the SPAR (6,7,12). There are, in addition, descriptions of other, novel methods for hearing loss identification and prediction by the acoustic reflex, including regression equations (2,16,21) and a bivariate plot coordinate system (9, 17,20).…”
mentioning
confidence: 99%
“…Hearing loss prediction by the acoustic reflex, although an objective procedure, is apparently influenced by a variety of factors, including degree of hearing loss (6,13,15,17,22), central auditory dysfunction (17), subject age (6-8, 12, 13), and minor middle ear dysfunction (6)(7)(8)13). Of these factors, age and minor middle ear dysfunction have been associated specifically with a reduction in predictive accuracy for the SPAR methods (6,7).…”
mentioning
confidence: 99%